Alien transmissions in short waves: how radio stations from socialist countries covered Brazil during the Cold War - Pieranti, Octavio Penna [UNESP]; Lima, Flavio Ferreira (Univ Federal Sergipe, 2023)
In the second half of the 1970s, the military dictatorship created Radiobras and Radio Nacional da Amazonia to confront shortwave radio stations from socialist countries that transmitted to Brazil. This article aims to analyze the coverage maps of seven of these stations, based on their real technical data and technological tools unavailable at that time. Brief comments are also made on the audience of these stations in Brazil. The paper points out that, in fact, the coverage was good, but there were difficulties related to the hab- its of listening to these programs by the Brazilian population.
Keywords: Radiobras; Amazon National Radio; Short waves; coverage maps; Cold War